1995
DOI: 10.1128/iai.63.12.4862-4867.1995
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha mediates resistance to Trypanosoma cruzi infection in mice by inducing nitric oxide production in infected gamma interferon-activated macrophages

Abstract: Cell invasion by Trypanosoma cruzi and its intracellular replication are essential for continuation of the parasite life cycle and for production of Chagas' disease. T. cruzi is able to replicate in nucleated cells and can be killed by activated macrophages. Gamma interferon (IFN-␥) is one of the major stimuli for the activation of macrophages and has been shown to be a key activation factor for the killing of intracellular parasites through a mechanism dependent upon nitric oxide (NO) biosynthesis. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
1
11

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(148 citation statements)
references
References 36 publications
6
120
1
11
Order By: Relevance
“…Control of Chagas infection requires both humoral and cell-mediated immunity directed by a type 1 cytokine response (Kumar and Tarleton, 1998). Endogenous IFN-g and TNFa play critical roles in the control of the infection through a mechanism including release of free radicals (Silva et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Control of Chagas infection requires both humoral and cell-mediated immunity directed by a type 1 cytokine response (Kumar and Tarleton, 1998). Endogenous IFN-g and TNFa play critical roles in the control of the infection through a mechanism including release of free radicals (Silva et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that IFN-g-and TNF-a-activated macrophages control of the replication of T. cruzi in various hosts [20]. The mechanism by which macrophages are able to kill intracellular parasites has been shown to be dependent on NO [8][9][10][11][12][13]20], although a recent study using T. cruzi strains Tulahuen and Brazil suggested that inducible NO synthase (iNOS) is not required to control parasite replication in vivo [21]. However, much less is known about the mechanisms governing the migration of leukocytes to sites of tissue infection, especially to hearts of infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, infection with T. cruzi was accompanied by a parasite-associated increase in the expression of CCR5 and migration of T cells to infected tissues, in which several CCR5-acting chemokines are produced. The increased expression of CCR5 could be due to the production of IFN-g [28,29], TNF-a [8,30], interleukin (IL)-10 [7,31], and/or IL-12 [30,32,33] that occurs after the addition of trypomastigote forms of T. cruzi to cultures of splenocytes or after the infection of mice. Indeed, CCR5 expression is positively regulated by these cytokines [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrastructural features of the macrophage activation such as increase in size, surface rufflings and amount of cytoplasmic organelles are recognized as an accurate indication of high phagocytic and microbicidal activities of these cells both in humans and experimental models (Anosa et al, 1997;El Shewemi et al, 1996;Takemura et al, 1989), including Chagas' disease (Melo and Machado, 2001;Melo et al, 2003). On the other hand, biochemical changes, as the ability of secreting hydrogen peroxide (Nathan, 1982;Nogueira and Cohn, 1978;Reed et al, 1987), tumor necrosis factor-alpha (Silva et al, 1995), nitric oxide (Vespa et al, 1994;Petray et al, 1995;Rodrigues et al, 2000) and interleukin-12 (Antunez and Cardoni, 2000) have been considered important markers of macrophage activity.…”
Section: Introductionmentioning
confidence: 99%